The Impact Of Tax Avoidance On Firm Value - Achmad Subagdja; Syahrudin, Muhammad; Liya Setiawati (Universitas Indonesia Membangun, 2024)
Taxes are crucial because the government uses them to fund public welfare and development. Tax revenue in 2022 demonstrates an equally dispersed economic recovery in Indonesia across a number of industries. However, due to a number of factors, including instances of tax avoidance and corporate practices that exploit technicalities in tax laws, Indonesia's tax collection has fallen short of its proper amount. This study sought to ascertain how tax evasion affected the company value of coal mining businesses that were listed between 2018 and 2021 on the Indonesia Stock Exchange. Panel data regression analysis techniques are employed in the data analysis method using the Eviews version 12 software. Choosing model estimates the Chow test, Hausman test, Langrange multiplier test, normality test, panel data regression test, and hypothesis testing is how data testing is done. The analysis concluded that there is no relationship between tax avoidance and corporate value.